Some aspects on the biology of Himantura bleekeri (Blyth) and Amphotistius imbricatus (Schneider) from Mumbai - Raje, Sadashiv Gopal (Indian Journal of Fisheries, 2011)
Himantura bleekeri and Amphotistius imbricatus are bottom carnivores, with crustaceans ranking first in the food items followed by teleosts, molluscs and polychaetes. Number of poorly fed individuals was high in both the species. These species breed throughout the year. The male : female ratio of H. bleekerifor 1989-’05 and of A. imbricatus for 1997-‘05 were 1:0.98 and 1:1.36 respectively. The length-weight relationship was: Log W= -8.7298 +2.7297 Log L for H. bleekeri and Log W = - 6.4691 +2.3119 Log L for A. imbricatus.